Recuperação de solo contaminado com petróleo pela técnica da bioestimulação - Silveira, Brenno Dayano Azevedo da (Universidade Federal Rural do Semi-Árido, 2016)
Among the environmental impacts caused by oil activities the oil leaks in the soil are cited, which cause damage to ecosystems and consequently negative effects to society. For recovery these areas bioremediation is an alternative, viable, effective, simple application and low-cost, uses microorganisms able to degrade contaminants, through the biostimulation strategy which is based on the optimization of environmental conditions to promote microbial activity. This study aimed to evaluate the effect of biostimulation with application of NPK fertilizer 10:30:20 on oil degradation in a Vertisol. The soil was artificially contaminated with oil in increasing levels of 0, 1, 3, 5 and 10 % mass base and the biostimulation was made with NPK fertilizer 10:30:20, single dose only in the beginning of the experiment in equivalent concentrations levels to 0, 250, 500, 1,250 and 2,500 kg ha-1. The control of contaminant degradation was realized by respirometric method, through the CO2 production measured every 7 days along the 91 days of experiment. It was observed higher CO2 production in the treatments with fertilizer, increased CO2 production in all treatments in the first 14 days of experiment and the mathematical model obtained by Response Surface Method was able to estimate the dose of NPK formulation 10:30: 20 for different petroleum contamination levels. It is concluded that the biostimulation technique with NPK fertilizer application in proportion 10:30:20 had a significant effect on the increase of CO2 production in Vertisoil with different levels of oil contamination by showing the positive effect of the biostimulation in the contaminant degradation optimization
Keywords: Biorremediação; Solo; Argiloso; Fertilizante; NPK; Bioremediation; Soil; Clay; Fertilizer; NPK; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE